Elementos formais, texturais e interpretativos nas sonatas para piano de João Domingos Bomtempo (1775-1842) - Bacovis, Andrey Costa [UNESP] (2017)
This research aims at the presentation of a stylistic overview of the João Domingos Bomtempo’s piano sonatas, aiming the musical interpretation. In the first chapter, is presented a brief biography of this composer, focusing on his musical trajectory, his works and the composers with whom he had contact. The following chapter is dedicated to formal analyzes of his sonatas, contemplating especially the first movements, in which works by CAPLIN (1998), HEPOKOSKI & DARCY (2006) and ROSEN (1988) were the main references. In the third chapter, the texture elements of his sonatas are investigated, from the association with the specialized literature in interpretive practices, especially those that deal with the musical style of the composers of the London Pianoforte School, with whom Bomtempo had contact. Finally, the last chapter associates the content of previous chapters in order to make an interpretative proposal for Bomtempo’s Sonata opus 15 n.1. In this research, it is possible to see a way in which formal and textural aspects of a musical work can be emphasized in a musical performance in order to enrich the musicality, providing interpretive possibilities.